Impact of Nutrition and Sociodemographic Factors on Students from Public Universities - Tamayo, Verónica Patricia Sandoval; Manzano, Angélica María Solís; Samaniego, María Victoria Padilla; Caluña, Edgar Rolando Morales; González , Katherine Denisse Suárez (Journal of Ecohumanism, 2025)
The study evaluates how diet and sociodemographic factors affect the body composition of university students. Body composition is critical for health and well-being, especially among university students. Factors such as nutrition and sociodemographic elements significantly influence it. The study employed a cross-sectional design with a sample of 171 students. Bioimpedance techniques were used to assess body composition, and detailed questionnaires collected dietary and sociodemographic information. Advanced statistical analyses were conducted to identify significant correlations and trends. A total of 15.79% of the students had a very high fat intake, and only 1.75% met the standards for a nutrient-rich diet. Among males, a nutrient-rich diet was positively correlated with a higher percentage of muscle mass and a smaller hip circumference. Residence location significantly affected arm circumference in females, being higher among those living in urban areas. The study highlights the high prevalence of diets high in fat and low in nutrients among students, emphasizing the need to promote balanced eating habits. Gender differences suggest that nutritional interventions should be tailored accordingly. Additionally, residence location influences body composition, indicating variations in dietary traditions and access to healthy foods. These findings can guide policies and intervention programs at universities to improve the health and well-being of university students in Ecuador.